Legal Protection for Workers Experiencing Workplace Accidents and Corporate Liability (Case Study of PT ASL Shipyard Indonesia) - Evellyn Abigael Rhemrev (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
Workplace accidents are a problem that cannot be separated from industrial relations and are prone to occur. This case study examines the implementation of occupational safety and health (OSH) at PT ASL Shipyard Indonesia, as well as the forms and limitations of the company’s legal responsibility in workplace accidents that result in losses for workers. As a normative juridical study, statutory and case approaches are used. The results of the study indicate that companies must implement OSH consistently to protect the workers. The company’s responsibility for workplace accidents includes preventive and repressive measures, as well as a civil and criminal liability. The workplace accident that occurred at PT ASL Shipyard show negligence in the implementation of safety standards, particularly in terms of supervision and the execution of safety procedures. Therefore, to improve worker protection and minimize the risk of workplace accidents, it is necessary to strengthen the implementation of OSH and ensure consistent law enforcement.